2007
DOI: 10.1258/095646207781439748
|View full text |Cite
|
Sign up to set email alerts
|

Experience of delivering women with HIV in an inner city London hospital 1994–2004

Abstract: The objective of this study was to compare deliveries in women with HIV at Homerton University Hospital with those in the general antenatal hospital population. The study was a retrospective case-note review of deliveries from 1994 to 2004 at an Inner City London Hospital, UK (Homerton University Hospital). In all, 113 deliveries were studied in 98 women with HIV. Compared with the general antenatal population, women with HIV were more likely to be from African backgrounds, describe inadequate housing and be w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
3
6
1
2
Order By: Relevance
“…At 13%, the present study had a relatively low proportion of women with a viral load of more than 50 copies per mL at delivery compared with other studies [16,17,[19][20][21]. Two studies from London reported the highest rates of detectable viral load at delivery: 38% [16] and 45% [17].…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…At 13%, the present study had a relatively low proportion of women with a viral load of more than 50 copies per mL at delivery compared with other studies [16,17,[19][20][21]. Two studies from London reported the highest rates of detectable viral load at delivery: 38% [16] and 45% [17].…”
Section: Discussioncontrasting
confidence: 61%
“…Two studies from London reported the highest rates of detectable viral load at delivery: 38% [16] and 45% [17]. Timing of antiretroviral initiation is key to ensure that the viral load is less than 50 copies per mL by delivery, with earlier initiation warranted when the viral load is high in early pregnancy [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rund 13. (18,6%) waren Frauen, etwa zwei Drittel waren zwischen 20 und 40 Jahren alt, also in einem Alter, in dem eine Schwangerschaft eintreten kann [2]. In den Jahren von 1999 bis 2005 wurden in 10 deutschen Zentren etwa 600 Schwangere mit einer HIV-Infektion betreut, 98,4% wurden per Sectio caesarea entbunden [3].…”
unclassified
“…Bei etwa der Hälfte dieser Frauen waren die Bedingungen für eine vaginale Entbindung nach den neuen Leitlinien 2008 gegeben. Im gleichen Zeitraum wurden in anderen europäischen Län-dern und den USA zwischen 20 und 75% der HIV-positiven Schwangeren mit optimalen Voraussetzungen auf normalem Wege entbunden [4,5,6,7,8]. Nachdem sich 2008 die "Deutsch-österreichischen Empfehlungen zur HIV-Therapie in der Schwangerschaft und bei HIV-exponierten Neugeborenen" [1] hinsichtlich einer möglichen vaginalen Geburt bei einer HIV-Infektion änderten, wurden in drei deutschen Zentren 293 Kinder von HIVpositiven Müttern entbunden [9].…”
unclassified